PEMASARAN LINTAS BUDAYA MELALUI IKLAN PRODUK MAKANAN INDONESIA DI NEGARA-NEGARA ARAB - Febryana, Dhannya (UI Scholars Hub, 2025)
This paper analyzes the media discourse surrounding advertisements for Indonesian food products, such as the instant noodle brand Indomie, in Arab countries. The expansion of Indonesian food products in international markets, including in Arab nations, is largely driven by effective and culturally adaptive marketing strategies. This study focuses on the analysis of television commercials and advertising posters, aiming to uncover how linguistic, semiotic, and sociocultural elements are employed to construct persuasive advertising messages. The method used is discourse analysis, with data comprising transcripts of television advertisements and visual elements from promotional posters. The advertising strategies of these products seek to bridge cultural gaps by tailoring marketing messages to align with local values and preferences, despite the potential disparity between the idealized imagery constructed and the actual consumption realities. This study offers valuable insights into the significance of cultural adaptation in global marketing and its impact on consumer reception.